LEGAL SOURCES IN RISK ASSESSMENT AT THE WORK PLACE AND WORK ENVIRONMENT - Ćosić, Dragana (Law - Theory and Practice, 2010)
Safety and health at work as a protection system of employees and especially the risk assessement at the work place is defined by the Law on safety and health at work, as well as a serious of sublegal acts. Provisions in article 13 of the Law, determine the responsibilities of each employer to pass an a on risk assesment in written form for all work places as well as to assess the means and measures for addressing them.